Postoperative radiotherapy (PORT) for early oral cavity cancer (pT1-2, N0-1): A review. (November 2019) - Ivaldi, Eliana; Di Mario, Dalila; Paderno, Alberto; Piazza, Cesare; Bossi, Paolo; Iacovelli, Nicola Alessandro; Incandela, Fabiola; Locati, Laura; Fallai, Carlo; Orlandi, Ester
Highlights: No high-quality data clearly guide the indications for PORT in early stage OSCC Patients with multiple mAPFs tend to have poorer outcomes and to benefit from PORT A proper PNI classification may help in identifying high-risk patients needing PORT In patients with pN1 and ENE, the recommended treatment is PORT plus Chemotherapy Abstract: Early stage (T1-2, N0-1) oral squamous cell carcinoma (OSCC) has a generally favorable prognostic outcome. However, locoregional recurrences can occur in up to 30–35% of patients, and 20% will eventually die of disease. National and international treatment guidelines do not recommend the use of postoperative radiotherapy (PORT) in a setting of early OSCC, and highlight surgery alone as the standard single modality treatment. Notwithstanding, the negative prognostic impact of some adverse pathological features, such as perineural and lymphovascular invasion, poor differentiation, depth of invasion >4 mm, and presence of nodal metastasis, is well known. The advantages of PORT in such scenarios are still debated. The aim of this study was to review the more recent literature to provide evidence on the benefits of PORT in the context of early stage OSCC.